A Simple, Universal, and Cost-Efficient Digital PCR Method for the Targeted Analysis of Copy Number Variations. (1st September 2019) - Cassinari, Kévin; Quenez, Olivier; Joly-Hélas, Géraldine; Beaussire, Ludivine; Le Meur, Nathalie; Castelain, Mathieu; Goldenberg, Alice; Guerrot, Anne-Marie; Brehin, Anne-Claire; Deleuze, Jean-François; Boland, Anne; Rovelet-Lecrux, Anne; et al.
Abstract: BACKGROUND: Rare copy number variations (CNVs) are a major cause of genetic diseases. Simple targeted methods are required for their confirmation and segregation analysis. We developed a simple and universal CNV assay based on digital PCR (dPCR) and universal locked nucleic acid (LNA) hydrolysis probes. METHODS: We analyzed the mapping of the 90 LNA hydrolysis probes from the Roche Universal ProbeLibrary (UPL). For each CNV, selection of the optimal primers and LNA probe was almost automated; probes were reused across assays and each dPCR assay included the CNV amplicon and a reference amplicon. We assessed the assay performance on 93 small and large CNVs and performed a comparative cost-efficiency analysis. RESULTS: UPL-LNA probes presented nearly 20000000 occurrences on the human genome and were homogeneously distributed with a mean interval of 156 bp. The assay accurately detected all the 93 CNVs, except one (<200 bp), with coefficient of variation <10%. The assay was more cost-efficient than all the other methods. CONCLUSIONS: The universal dPCR CNV assay is simple, robust, and cost-efficient because it combines a straightforward design allowed by universal probes and end point PCR, the advantages of a relative quantification of the target to the reference within the same reaction, and the high flexibility of the LNA hydrolysis probes. This method should be a useful tool for genomic medicine, which requires simple methods for the interpretation and segregation analysis of genomic variations.